Litigating Socio-Economic Rights in South Africa: A choice between corrective and distributive justice - Christopher Mbazira (Pretoria University Law Press (PULP), 2009)
Litigating Socio-Economic Rights in South Africa: A choice between corrective and distributive justice by Christopher Mbazira 2009 ISBN: 978-0-9814124-7-4 Pages: viii 273 Print version: Available Electronic version: Free PDF available